The journey from discovery to scientific change: scientific communities, shared models, and specialised vocabulary - Roe, Sarah M (International Studies in the Philosophy of Science, 2017)
Scientific communities as social groupings and the role that such communities play in scientific change and the production of scientific knowledge is currently under debate. I examine theory change as a complex social interaction among individual scientists and the scientific community, and argue that individuals will be motivated to adopt a more radical or innovative attitude when confronted with striking similarities between model systems and a more robust understanding of specialised vocabulary. Two case studies from the biological sciences, Barbara McClintock and Stanley Prusiner, help motivate the idea that sharing of models and specialised vocabulary fill the gap between discovery and scientific change by promoting the dispersal of important information throughout the scientific community. © 2017 Open Society Foundation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-085-635-391-358 tex.type: [object Object]
Keywords: dept.his

Extended mechanistic explanations: expanding the current mechanistic conception to include more complex biological systems - Roe, Sarah M; Baumgaertner, Bert (Journal for General Philosophy of Science, 2017)
Mechanistic accounts of explanation have recently found popularity within philosophy of science. Presently, we introduce the idea of an extended mechanistic explanation, which makes explicit room for the role of environment in explanation. After delineating Craver and Bechtel’s (2007) account, we argue this suggestion is not sufficiently robust when we take seriously the mechanistic environment and modeling practices involved in studying contemporary complex biological systems. Our goal is to extend the already profitable mechanistic picture by pointing out the importance of the mechanistic environment. It is our belief that extended mechanistic explanations, or mechanisms that take into consideration the temporal sequencing of the interplay between the mechanism and the environment, allow for mechanistic explanations regarding a broader group of scientific phenomena. © 2016, Springer Science+Business Media Dordrecht.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/167-521-013-773-230 tex.type: [object Object]
Keywords: Complex systems; Explanation; Mechanism; Mechanistic environment; dept.his

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
2 citations (Crossref) [2023-10-31] http://www.ncbi.nlm.nih.gov/pubmed/34111819 ; https://europepmc.org/article/MED/34111819 ; https://philpapers.org/rec/ROEUTR ; https://www.ncbi.nlm.nih.gov/pubmed/34111819
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Changing Working Environments in Philosophy: Reflections from a Case Study - McConwell, Alison; Bogacz, Magdalena; Brecevic, Char; Haber, Matthew; Wu, Jingyi; Roe, Sarah (Philosophy of Science, 2025)
Abstract There is an “underrepresentation problem” in philosophy departments and journals. Empirical data suggest that while we have seen some improvements since the 1990s, the rate of change has slowed down. Some posit that philosophy has disciplinary norms making it uniquely resistant to change. We present results from an empirical case study of a philosophy department that achieved and maintained male-female gender parity among its faculty as early as 2014. Our analysis extends beyond matters of gender parity because that is only one, albeit important, dimension of inclusion. We build from the study to reflect on strategies that may catalyze change.
Keywords: Computer science; Epistemology; Philosophy; Sociology; dept.his; peer-reviewed